2021
DOI: 10.21203/rs.3.rs-992412/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Developing a mobile application to improve the quality of life among breast cancer survivors

Abstract: Background In recent years, there has been a growing recognition of the value of mobile applications for health. The current study explored key factors that drive use of mobile applications among breast cancer survivors,. Methods We conducted in-depth interviews with a convenience sample of 14 ethnically diverse cancer survivors and individuals in their support systems. Interviewees included six breast cancer survivors, one survivor of a different type of cancer, and four individuals in their support systems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Such features can significantly contribute to enhancing patients’ well-being [ 57 ]. Additionally, studies have found that these apps can improve communication with health care providers and improve self-efficacy and quality of life [ 30 , 58 ]. However, it is important to note that the quality and accuracy of the information provided by these apps can vary, and it is recommended to consult with a health care professional before using any app for managing a medical condition.…”
Section: Discussionmentioning
confidence: 99%
“…Such features can significantly contribute to enhancing patients’ well-being [ 57 ]. Additionally, studies have found that these apps can improve communication with health care providers and improve self-efficacy and quality of life [ 30 , 58 ]. However, it is important to note that the quality and accuracy of the information provided by these apps can vary, and it is recommended to consult with a health care professional before using any app for managing a medical condition.…”
Section: Discussionmentioning
confidence: 99%